PENGARUH SALES PROMOTION, POSITIVE EMOTIONS DAN HEDONIC SHOPPING TERHADAP IMPULSE BUYING MELALUI E-COMMERCE PADA MASYARAKAT SURAKARTA - Siti Fatimah Susi Tri Fabriana; Ari Susanti (Journal of Management Small and Medium Enterprises (SMEs), 2023)
The purpose of this study was to identify and analyze the impact of Promotions, Positive Emotions, and Hedonic Shopping on Impulse Buying through e-commerce in Surakarta. The phenomenon of e-commerce is very helpful for people to buy, especially how to buy, to be quite convenient, and to meet customers’ needs. Data analysis in this study was performed using Multiple Linear Regression tests, using the data processing program SPSS version 21. The sample for this study consisted of 170 respondents. The results of this study show that Hedonic Shopping has a significant positive effect on Impulse Buying via e-commerce in Surakarta City, while Sales Promotion and Positive Emotions have negative and negligible effects. Keywords: Impulse Buying; Sales Promotion; Positive Emotions; Hedonic Shopping